2013
DOI: 10.1517/14712598.2014.866085
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular gene therapy for myocardial infarction

Abstract: Introduction Cardiovascular gene therapy is the third most popular application for gene therapy, representing 8.4% of all gene therapy trials as reported in 2012 estimates. Gene therapy in cardiovascular disease is aiming to treat heart failure from ischemic and non-ischemic causes, peripheral artery disease, venous ulcer, pulmonary hypertension, atherosclerosis and monogenic diseases, such as Fabry disease. Areas covered In this review, we will focus on elucidating current molecular targets for the treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 134 publications
(137 reference statements)
0
35
0
Order By: Relevance
“…Although clinical treatment continues to be improved over the past decades, the pandemic continues to show an upward trend [18]. Recently, due to increased insight into the molecular mechanisms of cardiovascular diseases, gene therapy has been proposed as a promising therapeutic tool for MI [19]. In this study, CD151 delivery was revealed to be beneficial as a treatment of MI, and US microbubble was able to improve its delivery efficiency.…”
Section: Discussionmentioning
confidence: 88%
“…Although clinical treatment continues to be improved over the past decades, the pandemic continues to show an upward trend [18]. Recently, due to increased insight into the molecular mechanisms of cardiovascular diseases, gene therapy has been proposed as a promising therapeutic tool for MI [19]. In this study, CD151 delivery was revealed to be beneficial as a treatment of MI, and US microbubble was able to improve its delivery efficiency.…”
Section: Discussionmentioning
confidence: 88%
“…For a detailed review of methods used to achieve stable cardiac-specific gene transfer, the reader is referred to excellent reviews on the subject [97, 98]. Major considerations include whether transient or chronic gene expression is needed, which specific cell type requires modification, and whether gene transfer is to be applied locally or globally.…”
Section: Expert Opinion: Gene Therapy For Arrhythmias In Hfmentioning
confidence: 99%
“…We focus on proteins as potential therapies to repair and regenerate damaged cardiac tissue. Gene and cell-based therapies are thoroughly reviewed elsewhere [3, 7-11]. Additionally, we focus on the complexity of tissue regeneration and repair processes and reasons for more comprehensive therapies.…”
Section: Introductionmentioning
confidence: 99%